Conjugate natural convection in a cavity with a conductive partition and filled with different nanofluids on different sides of the partition (vol 216, pg 67, 2016) - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier Science Bv, 2016)
[Abstract Not Available]